Effectiveness of Diabetic Foot Exercise in Preventing the Risk of Diabetic Foot Ulcers in Type 2 Diabetes Mellitus Patients: Literature Review - Yusnaeni, Yusnaeni; Fajriansih, Andi (Master of Public Health Program Universitas STRADA Indonesia, 2021)
Diabetic foot ulcers are one of the most common complications in diabetic patients and cause 10% of patients undergo amputation. One of the efforts to prevent the risk of more severe complications is diabetic foot exercises to reduce the risk to patients and the economic burden it causes to society. This literature review aims to summarize, assess and synthesize study results regarding the effectiveness of diabetic foot exercises in preventing the risk of diabetic foot ulcers in type 2 diabetes mellitus patients. This study used a literature review method. The literature search strategy used the database pubmed, proquest, science direct, and the cochrane library in the period 2010-2020. From 4 databases, 97 relevant articles were obtained. The exclusion of duplicate articles, titles, abstracts, and research results was left with 5 articles. The results showed a significant difference between the size of diabetic foot ulcers in the intervention group at week 4 and 12 compared to the control group (p ≤ 0.05), the chance of reducing the risk of diabetic foot ulcers was 1.238 times in the intervention group (p= 0.001) , the difference in mean scores posttest in the intervention group and the control group after exercise for 6 times in 2 weeks was 9.24 (p = 0.002), after the intervention the risk of diabetic foot ulcers decreased by 82% (p = 0.001). Diabetic foot exercise is effective in preventing the risk of diabetic foot ulcers, and can reduce and accelerate wound healing in DM patients with diabetic foot ulcers